Awareness of ergonomics among plantation workers / Amirul Aiman Md Kamal Fatimi - Md Kamal Fatimi, Amirul Aiman (Faculty of Plantation and Agrotechnology, 2016)
Ergonomics is the study of work that involves workers. By undergoing a task ergonomically, one can reduce the risk of getting body disorder thus, preventing them from injured. Ergonomics seen as one of the major problems that suffered by almost all workers in OPP whether direct or indirectly. This study intends to determine the level of ergonomic awareness among plantation workers in ESPEK Plantation, Keratong based on knowledge of respondent, occupation exposure and education level of respondents. A total of 80 respondent were studied using survey based questionnaire which involves 45 FFB harvesters and 35 FFB loaders. This study will detennine the factors which contribute the highest in awareness of ergonomics among workers. Based on the demographic analysis, most of them only possess mediocre level of education. As the result being analyzed, knowledge becomes the most dominant factor towards their awareness to ergonomics. This study will give an insight ofwhich factor affects the level of awareness among OPP worker in ESPEK Plantation, Keratong.